Hubungan Antara Intensitas Penggunaan Facebook dengan Kecenderungan Nomophobia Mahasiswa BK Undana - Da Costa, Gabriela A.C; Pua Upa, Muhamad D; Masi, Lolang M; Nalle, Andriani P (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
The use of facebook and nomophobia has a very negative impact on students. This study aims to determine the description of the intensity of Facebook use with the nomophobia tendency of students, and whether there is a relationship between the intensity of facebook use and the nomophobia tendency of BK Undana students. This research uses a quantitative approach with a type of correlation descriptive research. This research was carried out at the Guidance and Counseling Study Program of FKIP Nusa Cendana University Kupang with a total population of 209 people and a sample of 70 people. The sampling technique used is the purposive sampling method or respondents who have the characteristics of the same criteria. The data collection technique uses a likert scale questionnaire. The data analysis techniques used are descriptive analysis and correlation analysis with the help of the SPPS for Windows 26.00 Version program. The results showed that (I) In general, students using Facebook are in an intermediate presentation, namely 43% for the low category in using Facebook (II) Based on the results of data analysis, the nomophobia tendency of students of the FKIP guidance and counseling study program at Nusa Cendana University is in the low category in the nomophobia tendency with a presentation of 44%. Person product moment correlation analysis shows that between the intensity of facebook use and the tendency to nomophobia has a positive directional relationship shown with an r value of 0.452 The results of the correlation significance test, showed that there was a significant relationship between the intensity of facebook use and the nomophobia tendency of students of the Guidance and Counseling Study Program FKIP Nusa Cendana Kupang University as evidenced by the r-count value > r table (0.452 >0.273). Based on the results of the study, it was concluded that there is a relationship between the intensity of Facebook use and the nomophobia tendency of BK Undana students. The higher the intensity of facebook use, the higher the tendency to nomophobia, on the contrary, the lower the intensity of facebook use, the nomophobia tendency of BK Undana students is also lower.